User intent perception by gesture and eye tracking. Issue 1 (31st December 2016) - Yang, Xian; He, Hanwu; Wu, Yueming; Tang, Chaolan; Chen, Heen; Liang, Jianbin
Abstract: User intent is a highly cohesive human activity which is difficult to encode and measure. It is critical to seize the target user's psychological expectations, feelings, needs, and other elements of user's true intentions in the area of product design. This paper proposes a task-based method to perceive user intent by capturing their "Hand movement" and "Eye movement" when target users are performing user tasks. In terms of "Hand movement", user intents are obtained through gesture recognition based on computer vision, in particular, task-based gesture recognition solves the classic difficult problem "Midas Touch" in gesture interface of computer vision; in terms of "Eye movement", user interests and concerns on product are captured by eye-tracking equipment. As the "Hand movement" and "Eye movement" represent the vast majority of user's nonverbal expression of intents, this method is proved to have great practicality and pertinence by both theory and experiment.